2020
DOI: 10.1109/access.2020.3024994
|View full text |Cite
|
Sign up to set email alerts
|

A Color Image Encryption Algorithm Based on One Time Key, Chaos Theory, and Concept of Rotor Machine

Abstract: An innovative method proposed for encrypting color images is comprised of one-time keys and chaos theory using a distinctive concept of rotor machine. The novelty of this scheme is that the rows and columns of 2-dimensional images are converted into circular object called rotor and can be rotated at 360 degrees in clockwise or anti clockwise direction. The rotation will change the existing rotor into new one and can be used in substitution process of plain image. This process can be repeated β times and each t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 81 publications
0
27
0
Order By: Relevance
“…Various design suggestions that make use of public key (asymmetric) encryption techniques were presented in some recent studies [49][50][51]. Similar to the design logic proposed in the study, other design studies have highlighted the key generator [52][53][54] and used best practices of modern cryptology science [55][56][57]. Quantum systems [58,59], fractional systems [60][61][62], and medical encryption algorithms [63][64][65], which have attracted attention recently, are other current topics related to design proposals.…”
Section: Analysis Of Proposed Architecturementioning
confidence: 86%
See 1 more Smart Citation
“…Various design suggestions that make use of public key (asymmetric) encryption techniques were presented in some recent studies [49][50][51]. Similar to the design logic proposed in the study, other design studies have highlighted the key generator [52][53][54] and used best practices of modern cryptology science [55][56][57]. Quantum systems [58,59], fractional systems [60][61][62], and medical encryption algorithms [63][64][65], which have attracted attention recently, are other current topics related to design proposals.…”
Section: Analysis Of Proposed Architecturementioning
confidence: 86%
“…Various design suggestions that make use of public key (asymmetric) encryption techniques were presented in some recent studies [49][50][51]. Similar to the design logic proposed in the study, other design studies have highlighted the key generator [52][53][54] and used best practices of modern cryptology…”
Section: Analysis Of Proposed Architecturementioning
confidence: 88%
“…10, clearly showing that the decrypted images are noisy but perceptible. We also compared the results with different methods [32], [39][40] in Table 7, which indicate that our proposed scheme has better reconstruction quality. Hence our proposed scheme is resistant to several noise attacks.…”
Section: Noise Attackmentioning
confidence: 99%
“…Rehman et al [144] proposed an image encryption algorithm that uses a one-time-key to generate chaotic maps using the hash of the plaintext image. The algorithm employs a novel concept known as a rotor machine, and through simulation, the results showed that the algorithm possesses strong cryptographic properties.…”
Section: One-time Keymentioning
confidence: 99%